68Ga-labelled recombinant antibody variants for immuno-PET imaging of solid tumours - Eder, Matthias; Knackmuss, Stefan; Le Gall, Fabrice; Reusch, Uwe; Rybin, Vladimir; Little, Melvyn; Haberkorn, Uwe; Mier, Walter; Eisenhut, Michael (European journal of nuclear medicine and molecular imaging, 2010)
Recombinant antibodies isolated from human antibody libraries have excellent affinities and high target specificity. As full-length IgGs are cleared inadequately slowly from the circulation, the aim of this work was to figure out which kind of recombinant antibody fragment proves to be appropriate for imaging epithelial cell adhesion molecule (EpCAM)-expressing tumours with the short-living radioisotope 68Ga.